Prevalence of KRAS, PIK3CA, BRAF and AXIN2 gene mutations in colorectal cancer and their relationship with dental agenesis: a systematic review - Francisco Sir-Mendoza; Meisser Madera; Farith González-Martínez (Revista de la Facultad de Medicina, 2021)
Introduction: The study of allelic and genotypic frequencies contributes to determining the distribution of genetic variants in different populations and their possible association with biomarkers. This knowledge could improve the decision-making process regarding the management of some diseases such as colorectal cancer (CRC), in which the detection of clinical biomarkers such as dental agenesis could be crucial in clinical practice.